New configurations of district heating and cooling system based on absorption and compression chillers driven by waste heat of flue gas from coke ovens. (15th February 2020) - Sun, Fangtian; Li, Junlong; Fu, Lin; Li, Yonghong; Wang, Ruixiang; Zhang, Shigang
Abstract: To recover waste heat for space heating and cooling, three new district heating and cooling systems based on absorption and compression chillers driven by waste heat of flue gas from coke ovens are proposed, and their significant differences are located in the energy station. The energy station of the first proposed scheme mainly consists of a double-effect absorption chiller, a single-effect absorption chiller, a water-to-water plate heat exchanger, a compression chiller for ice thermal energy storage, and a liquid desiccant regenerator. Compared with the first proposed scheme, the second proposed scheme has no liquid desiccant regenerator in the energy station. Compared with the second proposed scheme, the third proposed scheme has no single-effect absorption chiller in the energy station. The three proposed schemes are analyzed from the perspective of thermodynamic performance and financial benefit. The results show that among the three proposed schemes, the first proposed scheme has the highest thermodynamic performance, and the best financial benefit, and thus its configuration is optimal. The annual system coefficient of performance and annual product exergy efficiency of the first proposed scheme are about 19.8 and 44.1%, and its cost-effective transportation distance of waste heat can be up to 41.5 km. Highlights: Absorption chiller and compression chiller are used to upgrade cold energy in series. Energy cascade utilization helps to optimize process of district heating and cooling. Annual coefficient of performance of DHC-1 is about 136.5% higher than that of DHC-4. Annual product exergy efficiency of DHC-1 is about 32.1% higher than that of DHC-4. DHC-1 can save standard coal equivalent by about 25 kgce/m 2 during a year.